Consensus evidence-based clinical practice guide for the diagnosis and management of osteoporosis in childhood and adolescence - Yasser El Miedany; Hala Lotfy; Maha El Gaafary; Naglaa Gadallah; Annie Nasr Mehanna; Safaa Mahran; Waleed Hassan; Mohammed Hassan Abu-Zaid; Samar Abdelhamed Tabra; Mohamed Mortada; Ahmed R. Radwan; Dalia El Mikkawy; et al. (Egyptian Rheumatology and Rehabilitation)
Abstract Background The incidence of osteoporosis in children has increased dramatically during the last decade. This has been attributed to better survival rates of children living with chronic disorders, the increased use of medications known to have a negative impact on the children’s bones, and the increased preference for indoor activities and sedentary life in healthy children. Recent advances in pediatric osteoporosis definition, along with a lack of management recommendations or national consensus on its diagnosis and treatment, have led to a wide range of approaches being implemented to manage this illness. The aim of this work was to develop an optimal evidence-based consensus, target-oriented, on-steered therapeutic approach for children with osteoporosis. Based on 15 key clinical questions, a qualitative literature evaluation was conducted to provide evidence-based recommendations for the treatment of pediatric osteoporosis. An expert panel of 14 pediatric osteoporosis specialists conducted a Delphi survey. The level of evidence for each element was assessed using the Oxford Centre for Evidence-based Medicine (CEBM) System, when available, and/or based on the expert panel’s personal experience. All recommendations with an agreement rate of 75% or higher were included. Results Thirty-six recommendations, categorized into 13 domains, had evidence 4 or 5 and consequently were included in the Delphi survey. This was assessed online and a response rate of 82.4% was achieved. Delphi 2 round revealed that all the recommendations achieved 75% or more level of agreement and therefore have been accepted and included in this management recommendations. Based on that an algorithm showing an approach to pediatric osteoporosis management and maintenance of therapy has been developed. Conclusion For the management of children with osteoporosis, consulting a pediatric bone specialist is strongly advised, either by referral or by advice. This is extremely relevant because children are uniquely capable of recovering spontaneously or with the assistance of medication. This includes also vertebral fractures reshaping. Consequently, there is a huge opportunity to improve bone mass accretion and thus musculoskeletal health in children with osteoporosis.